2022
DOI: 10.46419/vs.53.5.5
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and physicochemical quality of honey in Bosnia and Herzegovina

Abstract: The aim of the study was to investigate the microbiological and physico-chemical quality of honey samples, sampled for the event “Honey Days in FB&H 2020”, which tested a total of 33 samples of different honey types from different geographical areas of Bosnia and Herzegovina (B&H). The aim of this study was to evaluate the relationship between physico-chemical properties and microbiological properties of the tested honey to assess quality. The submitted samples originated from both administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…has been reported by Matović et al and Gomes et al Yeast and mold counts in this study ranged from 4.0 × 10 2 to 2.6 × 10 5 cfu/g with Classic honey (H1 and H2) having the highest yeast and mold count. The yeast and mold count was also found in some Bosnia and Herzegovina honey samples that exceed the microbial criteria: EU regulations and Directive on microbiological criteria for food (2075/2013) …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…has been reported by Matović et al and Gomes et al Yeast and mold counts in this study ranged from 4.0 × 10 2 to 2.6 × 10 5 cfu/g with Classic honey (H1 and H2) having the highest yeast and mold count. The yeast and mold count was also found in some Bosnia and Herzegovina honey samples that exceed the microbial criteria: EU regulations and Directive on microbiological criteria for food (2075/2013) …”
Section: Discussionmentioning
confidence: 99%
“…Oftentimes, honey is manipulated by foreign sugars, so various standards have been legislated based on honey sugar contents to avoid its manipulation. , For instance, a recent study reported that 76.5% of honey imported into the Maldives was adulterated with various sugar syrups . Sugar is the major constituent in honey, comprising about 95% of honey dry matter. , Thus, carbohydrates share 73–83% constituents of honey, and among them, fructose and glucose are the most abundant . Water content is an indicator of honey stability and maturity .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations